Performance Evaluation Model in Companies with Linear and Matrix Structures - Rios Moreno, Victor Alejandro (2023)
This project aims to develop a performance evaluation model that serves as an application guide for companies with both linear and matrix structures. The project will primarily be conducted in three stages. The initial stage involves an analysis of organizational structures and an examination of various performance evaluation models and frameworks. Subsequently, in the second stage of the project, based on the findings from the analysis stage, the model proposal will be developed. Finally, in the third stage, validation will be carried out with experts to assess the feasibility of the proposal.